(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to identify the impact of dividend yield on stock price volatility moderating by ownership structure in the context of Pakistani stock exchange market. Researcher selected 40 listed non- financial companies of Pakistan stock exchange. Researcher selected secondary data for the research and applied panel data series to analyze the data. Further secondary data were analyzed through statistical package for social sciences (SPSS updated version). Conclusively, this study concluded positive impact of dividend yield on stock price volatility with p=0.021. Apparently, this research also concluded positive and significant moderating impact of ownership structure with dividend yield on stock price volatility in the context of Pakistan Stock Exchange. This research concluded that stock price volatility is strong predicator for financial decision making.